2021
DOI: 10.3389/fragi.2020.620382
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Biology of Protein O-GlcNAcylation: Approaches and Observations

Abstract: O-GlcNAcylation is a protein posttranslational modification that results in the addition of O-GlcNAc to Ser/Thr residues. Since its discovery in the 1980s, it has been shown to play an important role in a broad range of cellular functions by modifying nuclear, cytosolic, and mitochondrial proteins. The addition of O-GlcNAc is catalyzed by O-GlcNAc transferase (OGT), and its removal is catalyzed by O-GlcNAcase (OGA). Levels of protein O-GlcNAcylation change in response to nutrient availability and metabolic, ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 140 publications
(287 reference statements)
0
34
0
Order By: Relevance
“…Targeting integrin/FAK signaling is a potential strategy to treat fibrotic diseases including NASH [ 50 ]. Increased protein O -GlcNAcylation blocks insulin signaling and promotes lipogenesis [ 39 , 51 ]. IP6K1 inhibition may ameliorate metabolic dysfunction and NAFLD/NASH by altering these pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting integrin/FAK signaling is a potential strategy to treat fibrotic diseases including NASH [ 50 ]. Increased protein O -GlcNAcylation blocks insulin signaling and promotes lipogenesis [ 39 , 51 ]. IP6K1 inhibition may ameliorate metabolic dysfunction and NAFLD/NASH by altering these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Protein O -GlcNAcylation has been shown to differentially influence hepatic metabolism and fibrosis [ 39 , 51 ]. Heterozygous OGA- deleted mice (homozygous OGA -KO mice do not survive) develop metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of O-GlcNAcylation, this modification differs from N-and O-linked glycans since it is mainly present in cytosolic or nuclear proteins. Its function remains incompletely understood due to the lack of integrated studies of how O-GlcNAcomes are modulated and influence the other '-omic' components of healthy and/or pathological states [49]. Its importance in brain injuries is highlighted in TBI, in which an initial increase in this modification was seen (first 4 h post injury), whereas a decrease occurred after 12 h in a preclinical model.…”
Section: Cns-penetrating Injuriesmentioning
confidence: 99%
“…Downstream of glucose phosphorylation by hexokinase, the hexoamine biosynthesis pathway (HBP) generates O -GlcNAc to enable post-translational modification of proteins on Ser/Thr residues 110 . This post-translational modification is sensitive to nutrient availability and cellular stress 26 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 .…”
Section: Whole-organism Energetics and Potential Targets For Ad Thera...mentioning
confidence: 99%
“…Downstream of glucose phosphorylation by hexokinase, the hexoamine biosynthesis pathway (HBP) generates O -GlcNAc to enable post-translational modification of proteins on Ser/Thr residues 110 . This post-translational modification is sensitive to nutrient availability and cellular stress 26 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 . It has been observed that pharmacological inhibition of the enzyme that removes the O -GlcNAc from proteins resulted in more preserved tau O -GlcNAcylation, and decreased tau phosphorylation and aggregation 22 , 118 , 119 , 120 , 121 .…”
Section: Whole-organism Energetics and Potential Targets For Ad Thera...mentioning
confidence: 99%